2022
DOI: 10.1002/cbdv.202100958
|View full text |Cite
|
Sign up to set email alerts
|

Hantzsch‐Like Synthesis, DNA Photocleavage, DNA/BSA Binding, and Molecular Docking Studies of Bis(sulfanediyl)bis(tetrahydro‐5‐deazaflavin) Analogs Linked to Naphthalene Core

Abstract: The cyclocondensation reaction of aldehydes with dimedone and bis(6-aminopyrimidin-4-one) in acetic acid led to the formation of the corresponding bis (pyrimido[4,5-b]quinoline-4,6-diones) which are known as bis(sulfanediyl)bis(tetrahydro-5-deazaflavin) analogs in a single step. Also, bis(pyrimido[4,quinoline-4,6diones) which are linked to naphthyl core via phenoxymethyl linkage is prepared. The interactions of the synthesized compounds with DNA and bovine serum albumin (BSA) were studied. Gel electrophoresis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 133 publications
0
6
0
Order By: Relevance
“…A linear form (form III) that moves between forms I and II will be produced if both strands are severed. DNA degradation arises from extensive double‐strand breaks [33,64,65] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A linear form (form III) that moves between forms I and II will be produced if both strands are severed. DNA degradation arises from extensive double‐strand breaks [33,64,65] …”
Section: Resultsmentioning
confidence: 99%
“…Small molecules' ability to bind to DNA is typically stabilized by several non-covalent interactions, including lodging of molecules within base pairs (intercalation), molecules accommodation in the major or minor grooves, and through electrostatic interactions on the outside of the helix. [64,66,67]…”
Section: Dna Binding Studiesmentioning
confidence: 99%
“…In addition, 3-(furan-2-yl)-1H-pyrazoles (Andicsová et al 2018;Ryan et al 2020;Barus et al 2021) have been reported to have biologically interesting applications. Based on these findings, and in continuation of our study interest in bioactive heterocycle production (Mohamed et al 2017, 2021a, b, c, Sroor et al 2019Fathi et al 2021;Helmy et al 2021;Ragheb et al 2022;Salem et al 2022;Waly Eldeen et al 2022), we were inspired to synthesize the pyrazolyl-chalcones and evaluate their in vitro anti-cancer effectiveness against different human cancer cell lines with an emphasis on the novel two chalcones 7b, and 7c that proved strong and interesting cytotoxic effect against lung carcinoma (A549) cell line. To find their effect on the apoptotic process of cancer cells, many theoretical and experimental investigations were extensively performed.…”
Section: Introductionmentioning
confidence: 93%
“…Interestingly, halogenated derivatives were the best photocleavers among pyrazoles [42], as well as nitro-substituted trifluoromethyl pyrazoles [43]. Deazaflavin analogs linked to the naphthalene core (UV-A) [45] were also found to photocleave DNA, and quinolinium dicarbocyanine dyes (near IR) bearing a pentamethine bridge that was meso-substituted with halogen caused photodynamic cell damage [46,47]. The attachment of Anthranilic acid DACHZs (AA DACHZs, Figure 2, G, H) bear an additional functional amine group which contributes to their chemistry, biology and technology.…”
Section: Introductionmentioning
confidence: 99%